The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.virol.2013.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of A-type inclusion formation enhances cowpox virus replication in mice: Implications for orthopoxvirus evolution

Abstract: Some orthopoxviruses including cowpox virus embed virus particles in dense bodies, comprised of the A-type inclusion (ATI) protein, which may provide long-term environmental protection. This strategy could be beneficial if the host population is sparse or spread is inefficient or indirect. However, the formation of ATI may be neutral or disadvantageous for orthopoxviruses that rely on direct respiratory spread. Disrupted ATI open reading frames in orthopoxviruses such as variola virus, the agent of smallpox, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…A26L, also named p4c or CPXV159 protein, is required to direct intracellular mature virions (IMVs) into ATIs (33); the protein has a bridging function between the A25L matrix protein and IMVs containing the membrane-associated A27L (CPXV162 protein) (34). In addition, the capability to embed mature virions in the ATIs was recently shown to influence the virulence of CPXV (35). We showed that the RatPox09 p4c amino acid sequence (A26; CPXV159 protein) results in a 59-amino-acid (aa) truncation at the N terminus, which likely is responsible for the observed V Ϫ phenotype; in contrast, FM2292 harbors a full-length p4c gene (Fig.…”
Section: Isolation Of a Cpxv From A Common Volementioning
confidence: 99%
“…A26L, also named p4c or CPXV159 protein, is required to direct intracellular mature virions (IMVs) into ATIs (33); the protein has a bridging function between the A25L matrix protein and IMVs containing the membrane-associated A27L (CPXV162 protein) (34). In addition, the capability to embed mature virions in the ATIs was recently shown to influence the virulence of CPXV (35). We showed that the RatPox09 p4c amino acid sequence (A26; CPXV159 protein) results in a 59-amino-acid (aa) truncation at the N terminus, which likely is responsible for the observed V Ϫ phenotype; in contrast, FM2292 harbors a full-length p4c gene (Fig.…”
Section: Isolation Of a Cpxv From A Common Volementioning
confidence: 99%
“…While many notable poxviruses, including monkeypox and variola virus, contain disrupted versions of the P4c protein (or its homolog), the lack of inclusion body formation may suggest a positive infection advantage. Interestingly, recent evidence has suggested that interruption of the cowpox P4c protein enhances the pathogenicity in the lungs of mice, as well as viral replication [35]. Given that the P4c gene is fragmented in the majority of the Farm 2 SwCRV viral isolates, a farm where we see increased presentation of poxvirus lesions, as well as enhanced pathogenicity and prolonged infection, one hypothesis might be that this gene interruption is driving this phenomenon.…”
Section: Discussionmentioning
confidence: 91%
“…Sequences rendered nonfunctional due to the accumulation of mutations following decreased or negative selection pressure for protein function may be removed from the genome to reduce the burden of replicating nonfunctional DNA (63). The decrease in genome size of some poxviruses such as variola virus, ectromelia virus, and molluscum contagiosum virus has been hypothesized to be an important mechanism of adaptation toward a narrower host range (19,20,64,65). Genes required for replication within a particular host are maintained, perhaps with minor modifications most suited to that particular host, while genes required for replication in alternative hosts are inactivated and removed.…”
Section: Discussionmentioning
confidence: 99%